Parental Involvement and its Impact on Basic five pupil’s Academic Achievement in Aba-North Local Government Area, Abia, State, Nigeria - Dickson, Patience Zakaria; Ehiemere Francisca IFEOMA; Ijeoma Jessica Udegbue (RADINKA JAYA UTAMA PUBLISHER, 2024)
Abstract The participation and engagement of parents in theirs children education and educational activities which include communication, volunteering, learning at home, decision making, and emotional supporting The main objective of this study is to examine the parental involvement and its impact on basic five pupil’s academic achievement in Aba-north L.G.A, Abia State. The study adopted a descriptive survey research method. Three research questions were raised and three research hypotheses were formulated and tested at a 0.05 significant level. The population of the study consists of some selected public schools in Aba-north. Teachers and parents were used. Based on the data analyzed, the finding revealed the result of mean and standard deviation on the level of parental involvement in social studies education among basic five pupils. However, the agreed parents/guardians help pupils of basic five with social studies project and assignment with mean of 3.30 and standard deviation of .60. Also, the respondents strongly agreed that they provide resources to support social studies learning with a mean of 3.56 and standard deviation of .50. It was also observed that the parents/guardians social studies teacher work together to set academic goals with the mean of 3.40 and the standard deviation of .50. They agreed that they I enjoyed learning social studies because of their parents/guardians support them with the mean of 3.32 and standard deviation of .51. The respondents in item five agreed that they motivated to learn social studies because of their parents/guardians are involvement.